G298(P) Zika virus associated meningoencephalitis in children: are we under reporting?. (12th March 2018) - Oligbu, G; Pay, L; Fallaha, M; Ahmed, L; Oligbu, OE; Durojaiye, C
Abstract : Introduction: Since 2015, an outbreak of Zika Virus infection (ZiKV) has been reported in over 30 countries. Emerging evidence suggest ZikV causes a spectrum of neurologic diseases both directly and by secondary autoimmunity. In pregnancy, ZiKV is a well-known cause of congenital brain abnormalities, including microcephaly. 1 It has also been linked with Guillain-Barre syndrome. 2 However, its association with meningoencephalitis is not well described, especially in children. Methods: We undertook a systematic review of the English literature published from 1947 to August 2017 to evaluate the risk factors, distribution, pathogenesis, clinical presentation, management and outcomes of encephalitis following Zika virus infection. Data sources included MEDLINE, EMBASE, Cochrane library, and references within identified articles. We also searched the papers using the ISI web of knowledge, to identify relevant articles and conference proceedings. Results: We identified 167 potential studies, of which 16 were duplicates and 140 were excluded on the basis of title and abstracts (figure 1). There were 9784 with suspected ZiKV in all age groups. 1411 cases were confirmed ZiKV either by RT-PCR in plasma, CSF and urine, ELIZA or MRI. There were 26 (1.8%) cases of meningoencephalitis. Among eight studies reporting clinical characteristics and outcomes of 16 cases, the mean age was 43 years (Range 19–81) and 75% (n=12) of cases were male. 63% (n=10) of the cases required admission to ITU, with a crude case fatality rate of 12% (n=2). Conclusions and clinical implications: Complications from ZiKV, although uncommon, may be severe. With international spread, clinicians need to be aware that ZiKV may be associated with meningoencephalitis. Although our review found a paucity of evidence of Zika virus associated meningoencephalitis in children, standardising the collection and reporting for individual cases across regions and countries would further allow meaningful analysis of the data collected, enabling monitoring of trends over time.